ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI AKUNTABILITAS KEUANGAN DANA DESA DI KABUPATEN KEBUMEN - Eko Hari Suryono; Negina Kencono Putri; Umi Pratiwi (JIM UPB (Jurnal Ilmiah Manajemen Universitas Putera Batam), 2020)
This study is entitled the analysis factors effect of the financial report, the accessibility of financial report, and the transparency of budget to the financial accountability of village fund in Kebumen regency. This study aimed to examine the effect of the financial report, the accessibility of financial report, and the transparency of budget to the financial accountability of village fund in Kebumen regency. The population in this study is villages in Kebumen regency. Purposive sampling technique used in this study as many as 82 villages. Data collection in this study using a questionnaire survey and interviews. The data were processed using multiple linear regression analysis. The results of this study indicate that the financial report, the accessibility of financial report, and the transparency of budget have a positive effect on the financial accountability of village fund in Kebumen regency. Hope this study can be applied in Kebumen regency to improve the financial accountability of village fund through improved the financial report, the accessibility of financial report, and the transparency of budget.